2015
DOI: 10.1097/cin.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Social Media

Abstract: This work examines where 18- to 30-year-old college students seek health information on the Internet and how they determine site and message credibility. Using a qualitative methodology, five focus groups were conducted with 18- to 30-year-old college students, and transcripts were analyzed with MaxQDA text analysis software. The study revealed that 18- to 30-year-old college students have Internet health information source preferences, reasons for seeking health information on the Internet, and message design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 28 publications
(20 reference statements)
1
13
0
1
Order By: Relevance
“…Social media has been advocated as the key to health information access for college students (Prybutok & Ryan, 2015). Our survey of 930 participants confirmed that most (n = 905, 97.3%) students in our sample reported they had used a social networking site in the preceding 12 months.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Social media has been advocated as the key to health information access for college students (Prybutok & Ryan, 2015). Our survey of 930 participants confirmed that most (n = 905, 97.3%) students in our sample reported they had used a social networking site in the preceding 12 months.…”
Section: Discussionsupporting
confidence: 65%
“…Researchers have explored the usefulness of social media for health promotion on issues such as HIV prevention (Taggart, Grewe, Conserve, Gliwa, & Roman Isler, 2015), and studied how information pertinent to healthy behaviors (e.g., physical exercises) (Zhang et al, 2013) and unhealthy behaviors (e.g., substance abuse) (Krauss et al, 2015) are communicated online via social media. Exploring how social media can be used to improve health issues that impact young adults should be a national priority (Prybutok & Ryan, 2015) because these "digital natives" (Joiner et al, 2013) are quite familiar with sharing their thoughts, opinions and experiences with others through what is known as "electronic word-of-mouth" (Zhang et al, 2013). However, little is known about their information retrieval from public health agencies through social media pertinent to influenza and influenza vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recent research suggests that young people (ages 18-29) are less likely than older adults to hold negative attitudes toward COVID-19 vaccination. 24 Nevertheless, younger adults often rely on social media for health information 25 and tend to have low levels of health literacy. 26 Youth may therefore be particularly vulnerable to mis-and disinformation about COVID-19 vaccines spread via social media.…”
Section: Introductionmentioning
confidence: 99%
“…These issues and challenges make young adults search for health-related information via the Internet to cope with health-related concerns and stresses [ 27 - 29 ]. Young adults search health information for various purposes, such as learning about health conditions, seeking online support, looking for treatment options, and prevention and screening information [ 2 , 30 , 31 ], or see the Internet as an acceptable resource that offers anonymized information or support for sensitive conditions or symptoms [ 32 ].…”
Section: Introductionmentioning
confidence: 99%